A data-centric approach to feed search in blogs. (1st January 2012) - Tsai, Flora S.
The explosive growth of blogs creates a critical demand for information retrieval techniques to effectively search for required and meaningful information. This paper studied the blog distillation and feed search task in the TREC Blog Track, which was designed to search for the relevant feeds which have a principal and recurring interest in a particular topic or query. In this paper, a novel data-centric approach is proposed which achieved good results compared to others in the TREC Blog Track.